New interpretations of developmental psycbology regarding the determinants of conduct - Thorne, Cecilia (1994)
Two current positions in the field of human development are presented. On the one hand, Scarr' s theory abour the effects of genotype on environment is discussed. On the other hand, the ecological theory of Bronfenbrenner, which describes human developmenr as an interaction between the developing person and his/her environment. The author discusses some aspects of both positions that need furrher study in order ro prevent negarive effects and have a better understanding of child development, in third world countries.